Effects of Hyperbaric Oxygen on Metabolic Capacity of the Skeletal Muscle in Type 2 Diabetic Rats with Obesity - Naoto Fujita; Fumiko Nagatomo; Shinichiro Murakami; Hiroyo Kondo; Akihiko Ishihara; Hidemi Fujino (The Scientific World Journal)
We investigated whether hyperbaric oxygen enhances the oxidative metabolic capacity of the skeletal muscle and attenuates adipocyte hypertrophy in type 2 diabetic rats with obesity. Five-week-old male Otsuka Long-Evans Tokushima fatty (OLETF) and Long-Evans Tokushima Otsuka (LETO) rats were used as diabetic animals and nondiabetic controls, respectively, and assigned to control and hyperbaric oxygen groups. Animals in the hyperbaric oxygen group were exposed to an atmospheric pressure of 1.25 with an oxygen concentration of 36% for 3 h daily. The glucose level at 27 weeks of age was significantly higher in OLETF rats than in LETO rats, but the elevation was inhibited in OLETF rats exposed to hyperbaric oxygen. The slow-to-fast fiber transition in the skeletal muscle was observed in OLETF rats, but the shift was inhibited in OLETF rats exposed to hyperbaric oxygen. Additionally, the oxidative enzyme activity of muscle fibers was increased by hyperbaric oxygen. The adipocyte size was larger in OLETF rats than in LETO rats, but hypertrophied adipocytes were not observed in OLETF rats exposed to hyperbaric oxygen. Hyperbaric oxygen enhances glucose and lipid metabolism in the skeletal muscle, indicating that hyperbaric oxygen can prevent elevation of glucose and adipocyte hypertrophy in diabetic rats with obesity.